(untitled) (Triyuga Academic Journal, 2025)
This research explores the gendered dimensions of consumption patterns in the emerging disposable economy in Koshi Province, Nepal. As global luxury and fast-fashion markets infiltrate provincial regions, the traditional, cyclical economy of rural areas is being replaced by a throwaway consumption culture. Through a quantitative analysis of 2,000 respondents (1,000 males and 1,000 females), this study examines the differences in consumption habits between genders, exploring motivations, product categories, and sustainability awareness. The results indicate that both males and females in Koshi Province exhibit distinct consumption behaviors, with females primarily purchasing fashion and beauty-related items, while males favor electronics and automobiles. The study highlights a concerning trend toward non-sustainable consumption, with both genders showing low levels of environmental awareness. The findings point to a growing reliance on disposable products and its adverse effects on local economies, which are already under strain. Recommendations for policy interventions to promote sustainable consumption and protect local industries are discussed.